Chronic Activation of LXRα Sensitizes Mice to Hepatocellular Carcinoma. Issue 5 (3rd January 2022) - Xie, Yang; Sun, Runzi; Gao, Li; Guan, Jibin; Wang, Jingyuan; Bell, Aaron; Zhu, Junjie; Zhang, Min; Xu, Meishu; Lu, Peipei; Cai, Xinran; Ren, Songrong; et al.
Abstract : The oxysterol receptor liver X receptor (LXR) is a nuclear receptor best known for its function in the regulation of lipid and cholesterol metabolism. LXRs, both the α and β isoforms, have been suggested as potential therapeutic targets for several cancer types. However, there was a lack of report on whether and how LXRα plays a role in the development of hepatocellular carcinoma (HCC). In the current study, we found that systemic activation of LXRα in the VP‐LXRα knock‐in ( LXRαKI ) mice or hepatocyte‐specific activation of LXRα in the VP‐LXRα transgenic mice sensitized mice to liver tumorigenesis induced by the combined treatment of diethylnitrosamine (DEN) and 3, 3', 5, 5'‐tetrachloro‐1, 4‐bis (pyridyloxy) benzene (TCPOBOP). Mechanistically, the LXRα‐ responsive up‐regulation of interleukin‐6 (IL‐6)/signal transducer and activator of transcription 3 (STAT3) signaling pathway and the complement system, and down‐regulation of bile acid metabolism, may have contributed to increased tumorigenesis. Accumulations of secondary bile acids and oxysterols were found in both the serum and liver tissue of LXRα activated mice. We also observed an induction of monocytic myeloid–derived suppressor cells accompanied by down‐regulation of dendritic cells and cytotoxic T cells in DEN/TCPOBOP‐induced liver tumors, indicating that chronic activation of LXRα may have led to the activation of innate immune suppression. The HCC sensitizing effect of LXRα activation was also observed in the c‐MYC driven HCC model. Conclusion: Our results indicated that chronic activation of LXRα promotes HCC, at least in part, by promoting innate immune suppressor as a result of accumulation of oxysterols, as well as up‐regulation of the IL‐6/Janus kinase/STAT3 signaling and complement pathways. Abstract :